Diversity of Drought Tolerance in the Genus Vigna - Iseki, Kohtaro; Takahashi, Yu; Muto, Chiaki; Naito, Ken; Tomooka, Norihiko (Frontiers in Plant Science, 2018)
Wild relatives of crop plants are thought as reservoir of prominent genetic resources for abiotic stress tolerance. However, insufficient information on genetic variation and phenotypic traits restricts their use for crop breeding. This study focused on wild species of genus Vigna (family Fabaceae) originated from highly humid to arid regions. To clarify the diversity of drought tolerance during the vegetative stage, 69 accessions, including 15 domesticated and 54 wild accessions, were evaluated under two drought conditions of non-terminal and terminal stresses. In the non-terminal drought condition, the plants were grown in pipes of different heights where surface soil water content decreased faster in pipes with greater height. Relative shoot biomass was used for tolerance evaluation and we identified 19 drought tolerant accessions. Almost of them were wild accessions showing higher relative shoot biomass than that in the domesticated accessions. Domesticated species were mostly classified as drought susceptible but could be improved using tolerant conspecific wild ancestors with cross-compatibility. The tolerance was related with higher plant water status presumably due to small water consumption. However, the variation of drought tolerance could not be explained by simple tolerance factor alone, and other tolerance mechanisms such as deep rooting and increasing in root biomass were found in the tolerant accessions. In the terminal drought condition, the plants were grown in small pots, and the watering was stopped to expose them extreme and rapid soil water scarcity. The tolerance was evaluated as the number of days until wilting. However, the accessions found to be tolerant in the pot experiment were not the same as those in the pipe experiment. In this condition, plant water status was not related with the length of days to wilting. This indicates that different mechanisms are necessary for adaptation to each of the non-terminal and terminal drought conditions. Many accessions were tolerant to one of the conditions, although we identified that some accessions showed tolerance in both experiments. The great diversity in drought tolerance in the genus Vigna might serve to both improve crop drought tolerance and understand the mechanisms of adaptation in drought-prone environments.